¿Qué está pasando? Cómo la música le da forma a lo social. - Raussert, Wilfried (Ensayos InterAmericanos, 2020)
The book provides an innovative look at the relationship between music and the social. It traces the presence of music in the world of politics, identity politics, cultural heritage and art and literature. The book establishes music as a key actor in the processes of reinventing the social.